The accuracy of severity assessment tools designed for community acquired pneumonia among elderly patients with hospital acquired pneumonia - Rasheedy, Doha (Asian Journal of Medical Sciences, 2016)
Background: Pneumonia severity assessment is an essential initial step in the evaluation of patients with community acquired pneumonia. Many validated severity assessment tools were designed for use in this setting. However, there is no disease based validated scoring system are in use for hospital acquired pneumonia.Aims and Objectives: The aim of this study was to assess the validity for the use of PSI, CURB-65, and SMART-COP scores in elderly with hospital acquired pneumonia.Materials and Methods: Thirty patients with hospital acquired pneumonia and 41 patients with community acquired pneumonia were assessed using PSI, CURB-65, and SMART-COP scores. Short term outcomes were recorded i.e. in hospital mortality, or 30 days mortality and the need for mechanical ventilation or vasopressor drugs.Results: The 30 day mortality was 66.67% and 41.5% among HAP and CAP patients respectively. In both groups, the patients who died were older than the survivors; they had lower partial pressure of oxygen and Glasgow Coma Scale score. Moreover, they had higher heart rate and higher PSI, CURB 65, and SMART- COP scores. Among patient with community acquired pneumonia survivors had higher serum albumin while among patient with hospital acquired pneumonia, the survivors had lower fasting blood glucose.Conclusion: PSI predicted 30 day mortality and the use of mechanical ventilation but not the use of vasopressor drugs in hospital acquired pneumonia. SMART- COP and CURB 65 predicted the use of vasopressor drugs in this group.Asian Journal of Medical Sciences Vol. 7(3) 2016 65-71